Sex and age differences in mortality trends of gastric cancer among Hispanic/Latino populations in the United States, Latin America, and the Caribbean - J. Smith Torres-Roman; Christian S. Alvarez; Pedro Guerra-Canchari; Bryan Valcarcel; José Fabián Martinez-Herrera; Carlos A. Dávila-Hernández; Camila Alves Santos; Samara Carollyne Mafra Soares; Dyego Leandro Bezerra de Souza; M. Constanza Camargo (Elsevier, 2022)
Summary: Background: An up-to-date analysis of gastric cancer mortality among Hispanic/Latino populations is required for estimating disease burden and assessing the effectiveness of clinical and preventive strategies. Methods: We retrieved gastric cancer deaths between 1997 and 2017 (as available) from the Surveillance, Epidemiology, and End Results Program (United States Hispanics) and the World Health Organization databases (Puerto Rico, 16 Latin American and Caribbean countries). Joinpoint regression analysis was used to examine trends in age-standardized mortality rates (ASMR; per 100 000 person-years) and calculate average annual percent changes (AAPCs) by country (or territory), age group (25-49 and ≥50 years), and sex. Trends were compared to assess slope parallelism. Findings: In 2017, Chile (31·8), Colombia (24·3) and Costa Rica (24·3) had the highest ASMR of gastric cancer for men, while Guatemala (17·2), Peru (13·5), and Costa Rica (13·3) had the highest ASMR for women. Small-to-moderate mortality declines (AAPCs ranged −4 to −0.5%) were observed between 1997 and 2017. In almost all countries, trends decreased among individuals aged ≥50 years. However, age-specific trends were not parallel (p-values <0.05) in Brazil, Colombia, Mexico, the United States, and Venezuela for both men and women, and in five additional countries for only women; with a few countries showing stable or slightly increasing trends for individuals aged 25-49 years. Interpretation: Overall gastric cancer mortality rates in Hispanics/Latinos declined in the last two decades. However, there was a notable variation in trends by country, sex, and age group. Continued and targeted prevention efforts are needed to reduce the disease burden in these vulnerable populations. Funding: Universidad Cientifica del Sur, Peru, and National Cancer Institute, United States.